La Investigación en los Planes de Doctorado en Educación de las Universidades Peruanas - González Aguilar, Hugo (2020)
The present study analyzes the research of the doctorate study plans in education from the Peruvian universities licensed by SUNEDU which reach at an average of 30 universities and the same number of programs that have disseminated their plans through the website. A study based on categories have been carried out. It concludes that the study plans of doctorate programs in education haven’t been standardized with regard to the research courses and the respective academic terms, and stop from appearing student movement.